2005
DOI: 10.1016/j.ejvs.2005.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoabdominal Aortic Aneurysm Repair: Interplay of Spinal Cord Protecting Modalities

Abstract: tcMEP/SSEP monitoring has proved to be an excellent means of detecting spinal cord ischaemia during surgery on thoracoabdominal aortic aneurysms. The prognostic value of tcMEP monitoring should be considered superior to that of SSEP measurements, because of its direct and rapid response to spinal malperfusion. Through combined neurophysiological monitoring, vital parameter balancing and intraoperative interventions, spinal cord perfusion improves and recovery of tcMEP and SSEP is achievable, reducing the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Open surgical repair of the aortic arch, the descending and the thoracoabdominal aorta are invasive procedures with high morbidity and mortality rates [4,14]. ESI is a less invasive and effective treatment for high-risk patients showing a low complication rate [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open surgical repair of the aortic arch, the descending and the thoracoabdominal aorta are invasive procedures with high morbidity and mortality rates [4,14]. ESI is a less invasive and effective treatment for high-risk patients showing a low complication rate [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular stent-graft implantation (ESI) is a less invasive treatment of aortic pathologies, associated with lower morbidity and mortality rates than conventional open aortic repair [1][2][3][4]. Open surgical treatment of aortic diseases necessitates aortic cross-clamping and occasionally hypothermic circulatory arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Our experiences during open surgical TAA treatment have shown that this procedure is followed by a quick recovery of evoked potentials, and consequently, has a positive effect on the neurological outcome of our patients [8,9]. Therefore, we conclude that an early adjustment of ICP below 15 mmHg proves to be sensible also during future complex TAAendoluminal treatment.…”
Section: Discussionmentioning
confidence: 66%
“…Three main factors contribute to spinal cord injury: ischemia during aortic cross-clamping, unsuccessful reattachment of spinal cord-perfusing arteries, and cytotoxic damage caused by hypotension and reperfusion injury [2]. On account of the experiences of former studies [3][4][5][6][7][8][9], neurophysiologically monitored open surgery of TAA has proven to be of positive neurological outcome. However, the open surgical technique is associated with the severe risk of paraplegia and mortality.…”
Section: Introductionmentioning
confidence: 98%
“…This also indicates that spinal cord blood supply is unlikely to depend on a single segmental artery, and occlusion of one of these arteries may not be the only causative factor affecting SCI (8). Cerebrospinal fluid drainage is effective for preventing this complication (9) and should be considered to deploy a stent graft as short as possible.…”
Section: Discussionmentioning
confidence: 99%